The Effect of Ocular Perfusion Pressure on Retinal Thickness in Young People with Presumed Systemic Hypotension - Naazia Vawda; Alvin Munsamy (Vision, 2021)
Low ocular perfusion pressure (OPP) may increase the risk of optic neuropathy. This study investigated the effects of OPP on the ganglion cell complex (GCC) and optic nerve head-retinal nerve fibre layer (ONH-RNFL) thickness in presumed systemic hypotensives (PSH). Fifteen participants with PSH and 14 controls underwent automated sphygmomanometry and Icare tonometry to calculate OPP: mean OPP (MOPP), systolic OPP (SOPP), and diastolic OPP (DOPP). ONH-RNFL and macula GCC thickness were evaluated using the Optovue iVue optical coherence tomographer. Statistical analysis comprised independent t-tests, the Mann–Whitney U test and binary logistic regression analysis. There was no significant difference when comparing ONH-RNFL and macula GCC thickness between both groups. Increased MOPP (OR = 0.51; 95% CI: 0.27–0.97; p = 0.039) and SOPP (OR = 0.79; 95% CI: 0.64–0.98; p = 0.035) were significantly associated with a decreased risk of reductions in GCC total thickness. Increased SOPP (OR = 0.11; 95% CI: 0.01–0.89; p = 0.027) was significantly associated with a decreased risk of reductions in the average ONH-RNFL thickness. The study found no significant retinal thickness changes in PSH’s, in comparison to the controls. The study established that, by increasing MOPP and SOPP, there was a decreased risk of reductions in the total GCC thickness and average ONH-RNFL thickness. Higher SOPP may decrease the possibility of retinal thinning of the GCC and ONH-RNFL. However, higher MOPP may decrease the odds of thinning of the GCC before ONH-RNFL changes.